EKSPEKTASI GURU PAMONG DAN SISWA TERHADAP KEMAMPUAN MENGAJAR MAHASISWA PPL (PRAKTEK PENGALAMAN LAPANGAN) STAIN PAREPARE - Mujahidah, Hj. Hasnani dan Magdahalena (IAIN PAREPARE, 2017)
This study aims to determine the level of expectations pamong teachers and students on the ability of teaching of Field Experience Practices (PPL) in school. The object of this research is students and teachers pamong and school students who have become the location of PPL 2016. The method used in the sampling of this study is the method of snowballing so it is not mentioned clearly the object of research. For the process of data retrieval, researchers use the instrument of questionnaires, interview guides, and documentation. Data is processed by using descriptive analysis. The results showed that the level of expectations of teachers pamong against PPL students in terms of teaching the class good enough. An example of the interviews conducted in MAN 2 Parepare generally illustrates that the PPL students can almost be said to be the real teacher. They use cutting-edge teaching methods and apply fun learning concepts. In addition, when the questionnaire distributed to students it can be concluded that the average student experience the same thing in learning that is quite happy and motivated in learning. This is shown at the percentage of students that is about 80% - 90% said his approval in terms of motivation in learning. Furthermore, the ability of students in learning can be seen from the results / values obtained by students during the implementation of PPL. In general, the data show that the average student gets a very satisfactory score from the monitoring of the pamong teacher. The range is at the level of 71.52 - 95.56. Aspects of this assessment consists of three things: preparation of learning, practice and personal implementation.